(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Motor position control is employed in a variety of settings, including the workplace, the home, and manufacturing plants. The motor load is expected to account for about 70% of total electrical consumption. The motors utilised in this section have been used for a wide range of tasks, including traction loads, rotating machines, and position control. Printing heads in printers, hoist motors, 3D printers, CNC machines, and even more modern robotic surgical equipment use position controlled motors to communicate with the environment are all examples of position control. Position control is simply defined as a motor with a position encoder, such as a resistive encoder or an optical encoder that gives control signals to the controller, and a controller that regulates the power supplied to the motor using a power controller, such as a DC-DC regulator. In this project position control of a DC motor is done by using the Proportional-Integral-Derivative (PID) approach in Simulink. PID attempts to fix the disparity by calculating the error between the actual and desired locations and then creating a PWM (pulse width modulated) signal by which position can be adjusted. The system changes into a closed-loop when a PID algorithm is applied to it. Error developed by the DC motor as well as the motor’s orientation can be corrected to the desired position when PID controller is combined with DC motor. The PID values Kp, Ki, and Kd are fine-tuned using Z. Nichols principles and the t&e approach, and to manage the direction of the DC motor using optimum values the PID algorithm is fine-tuned.